Rancang Bangun Visualisasi SIG Berbasis Web Untuk Pemetaan Kondisi Ruas Jalan - Yoga Handoko Agustin; M.Nabil Naufal Nasrullah (Jurnal Algoritma, 2026)
Road infrastructure is a vital component in supporting community mobility and welfare, including in Garut Regency, which has an extensive road network with a high level of damage. The absence of a web-based spatial visualization system has led to limited transparency and efficiency in conveying information on road conditions. This study aims to design and develop a web-based geographic information system (WebGIS) to map road conditions and damage points in Garut Regency. This system utilizes official survey data from the Public Works and Public Housing Agency, which has been processed using QGIS and compiled in GeoJSON format. The system was developed using the Waterfall method, which consists of the stages of communication, planning, modeling, construction, and deployment. This system was built with open-source technologies such as Laravel, Leaflet.js, and PostgreSQL, and includes interactive visualization features for road segments, damage points, and road condition statistics. Testing results show that the system performs as expected with a System Usability Scale (SUS) score of 76.3, which falls into the “Good” category. This research contributes to strengthening the transparency and efficiency of spatial-based road condition information delivery in Garut Regency and provides a basis for further WebGIS development in delivering information that supports priority road repair planning.